Ultrasonography Assessments of Optic Nerve Sheath Diameter as a Noninvasive and Dynamic Method of Detecting Changes in Intracranial Pressure - Lijuan Wang; Limin Chen; Ying Chen; Li-yang Bao; Nannan Zheng; Yuzhi Wang; Yingqi Xing (2018)
Importance The crtierion standard method for monitoring intracranial pressure (ICP) can result in complications and pain. Hence, noninvasive, repeatable methods would be valuable. Objective To examine how ultrasonographic optic nerve sheath diameter (ONSD) correlated with noninvasive and dynamically monitored ICP changes. Design, Setting, and Participants The ONSD was measured before the lumbar puncture (LP) in 60 patients on admission. Patients with elevated ICP were divided into group 1 (200 < LP ≤ 300 mm H2O) and group 2 (LP > 300 mm H2O). Patients underwent follow-up ONSD and LP measurements within 1 month. We analyzed the correlations between the ONSD and ICP on admission and between the changes in ONSD and ICP, which were the respective changes in ONSD and ICP from admission to follow-up. Main Outcomes and Measures The ultrasonographic ONSD and ICP were measured on admission and follow-up. The correlations between the ONSD and ICP on admission and between the changes in ONSD and ICP were analyzed using Pearson correlation analyses. Results For 60 patients (Han nationality; mean [SD] age, 36.2 [12.04] years; 29 [48%] female) on admission, the ONSD and ICP values were strongly correlated, with anrof 0.798 (95% CI, 0.709-0.867;P < .001). Twenty-five patients with elevated ICP who completed the follow-up were included. The mean (SD) ONSD and ICP on admission were 4.50 (0.54) mm and 302.40 (54.26) mm H2O, respectively. The ONSD and ICP values obtained on admission were strongly correlated , with anrof 0.724 (95% CI, 0.470-0.876;P < .001). The mean (SD, range) changes in ICP and ONSD were 126.64 (52.51 mm H2O, 20-210 mm H2O) (95% CI, 106.24-146.07) and 1.00 (0.512 mm, 0.418-2.37 mm) (95% CI, 0.83–1.20), respectively. The change in ONSD was strongly correlated with the change in ICP, with anrof 0.702 (95% CI, 0.425–0.870;P < .001). The follow-up evaluations revealed that the elevated ICP and dilated ONSD had returned to normal, and no evidence of difference was found in the mean ONSDs between group 1 (3.49 mm; 95% CI, 3.34–3.62 mm) and group 2 (3.51 mm; 95% CI, 3.44–3.59 mm) (P = .778) at follow-up. Conclusions and Relevance The dilated ONSDs decreased along with the elevated ICP reduction. Ultrasonographic ONSD measurements may be a useful, noninvasive tool for dynamically evaluating ICP.